2016
DOI: 10.4137/ijtr.s37973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Kynurenine Metabolites on Respiratory Parameters of Rat Brain, Liver and Heart Mitochondria

Abstract: Previously, we demonstrated that the endogenous glutamate receptor antagonist kynurenic acid dose-dependently and significantly affected rat heart mitochondria. Now we have investigated the effects of L-tryptophan, L-kynurenine, 3-hydroxykynurenine and kynurenic, anthranilic, 3-hydroxyanthranilic, xanthurenic and quinolinic acids on respiratory parameters (ie, state 2, state 3), respiratory control index (RC) and ADP/oxygen ratio in brain, liver and heart mitochondria of adult rats. Mitochondria were incubated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 73 publications
(157 reference statements)
2
23
0
1
Order By: Relevance
“…Alterations of L-TRP metabolite levels in the blood found immediately after strokes indicate a significant activation of metabolism along the kynurenine pathway and increase the cardiovascular risk factor, as well [10][11][12]. In the line, we found that KYNA lowers the efficacy of mitochondria ATP synthesis of heart mitochondria [13,14].The aim of the study was to examine the Jerusalem Balsam action, whether this "natural mixture" has an ability to influence KYNA synthesis in the rat liver tissue, in an in vitro study. Subsequently we compared the effect of Jerusalem Balsam to the effect of Cerebrolysin [15] and D-cycloserine [16] in respect to inhibit KAT II activity in rat liver homogenate.…”
Section: Introductionsupporting
confidence: 71%
“…Alterations of L-TRP metabolite levels in the blood found immediately after strokes indicate a significant activation of metabolism along the kynurenine pathway and increase the cardiovascular risk factor, as well [10][11][12]. In the line, we found that KYNA lowers the efficacy of mitochondria ATP synthesis of heart mitochondria [13,14].The aim of the study was to examine the Jerusalem Balsam action, whether this "natural mixture" has an ability to influence KYNA synthesis in the rat liver tissue, in an in vitro study. Subsequently we compared the effect of Jerusalem Balsam to the effect of Cerebrolysin [15] and D-cycloserine [16] in respect to inhibit KAT II activity in rat liver homogenate.…”
Section: Introductionsupporting
confidence: 71%
“…Indole-3-acetate and l -kynurenine were recently shown to impair skeletal muscle mitochondrial ETS and select matrix dehydrogenases ( 34 ). Additionally, kynurenine and tryptophan-derived indole metabolites have been shown to decrease mitochondrial function (in vitro) in heart ( 38 , 39 ), kidney epithelial cells ( 54 ), liver ( 37 ), and skeletal muscle ( 55 ). These observations lend support to a hypothesis of uremic myopathy whereby muscle function and mitochondrial health may be related to the progressive accumulation of uremic metabolites consequent to GFR insufficiency ( 44 , 48 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has reported that some uremic metabolites can impair mitochondrial function (34,(37)(38)(39)(40). Based on these observations, Pearson correlation analyses were performed to identify metabolite features that were highly correlated with OXPHOS conductance (negatively and positively).…”
Section: Impaired Matrix Dehydrogenase Activity In Ckd Skeletal Musclementioning
confidence: 99%
“…Both kynurenines were able to abolish ROS production induced by copper; however, the toxic effect on mitochondrial and cellular function was enhanced by the coincubation of copper with both kynurenines. These effects may be due to the fact that both 3-HK and 3-HANA are able to affect respiratory control (oxygen consumption in states 2 and 3 of mitochondrial respiration) [ 61 ] in addition to copper toxicity in mitochondria. Both sceneries affect ATP production and can lead to cell death as can be observed in Figure 9() .…”
Section: Discussionmentioning
confidence: 99%